Internalizing Islamic Values in a Multicultural Context: A Case Study of Identity Preservation among Indonesian Migrant Children in Malaysia - Arfi Putri Maharani; Tamrin Fathoni; Miftaku Ni’amah; Neng Daris Salamah Elmi Putri Sibron (KURAS Institute, 2026)
Islamic Religious Education plays a crucial role in preserving the religious identity of Indonesian migrant children who grow up in multicultural environments with limited access to formal education. This study aims to detail the process of internalizing Islamic values to shape the Muslim identity of Indonesian migrant children at the Sungai Mulia 5 Gombak Learning Center (Sanggar Bimbingan) in Malaysia. Grounded in a constructivist perspective, this research emphasizes the subjective experiences and social interactions of migrant children as they navigate the internalization of Islamic educational values within a multicultural context. Utilizing a qualitative approach and a case study method, data were collected through semi-structured interviews with teachers, students, and learning center managers, alongside participatory observations. The findings reveal that the internalization of Islamic values is achieved through the integration of formal curricula and non-formal activities, such as daily worship practices and character-building exercises. This process unfolds through three systematic stages: value transformation, value transaction, and value trans-internalization, which collectively promote discipline, honesty, and responsibility among students. This research underscores the significance of non-formal educational institutions as vital havens for moral guidance and identity preservation for marginalized children living abroad. The results offer practical insights for similar educational providers seeking to enhance faith-based character development amidst the complexities of cultural diversity.